Men´s experiences of using anabolic androgenic steroids. Issue 1 (1st January 2021) - Börjesson, Annica; Ekebergh, Margaretha; Dahl, Marja-Liisa; Ekström, Lena; Lehtihet, Mikael; Vicente, Veronica
ABSTRACT: Purpose : Anabolic androgenic steroids (AAS) are used by men for their aesthetic and performance-enhancing effects and are associated with risk for side effects. Our research aims to deepen knowledge and understanding of men´s experiences of using AAS. Method : This phenomenological study is based on the reflective lifeworld research approach. Lifeworld interviews were conducted with twelve men about their experiences of using AAS. Results : By using AAS, men strive towards a muscular, strong and athletic ideal. Self-imposed demands, self-discipline and performance accelerate male physical development. The perfect male body ideal thus attained is fragile from both an existential and a biological perspective. The perfect self-image can easily be shattered by adversity. A man's very existence may be jeopardized if the use of AAS is revealed to others or if the body is let down by illness. Conclusions : Men´s use of AAS is a complex phenomenon. It partly concerns a traditional view of masculinity that is reflected in the community. It requires both broad and deep knowledge and understanding to be able to meet men using AAS in their problems and vulnerability; a meeting that is hampered by their low trust in healthcare, and by the fact that AAS are illegal.